Antitumor effects of Chinese herbal medicine compounds and their nano-formulations on regulating the immune system microenvironment - Sun, Kexiang; Wu, Linguangjin; Wang, Shuyun; Deng, Wanli (Frontiers in Oncology, 2022)
Traditional Chinese medicine, including herbal medicine, acupuncture and meditation, has a wide range of applications in China. In recent years, herbal compounding and active ingredients have been used to control the growth of a tumor, reduce suffering, improve survival quality, and prolong the life span of cancer patients. To reduce the after-effects, herbal medicine can be used in conjunction with radiotherapy and chemotherapy, or it might be an adjuvant to strengthen the immune effect of anti-cancer vaccines. Especially in the immunosuppressed tumor microenvironment, herbal medicine can perform anti-tumor effects by stimulating the immune response. This paper reviews the advances in research on anti-tumor immunomodulation in Chinese herbal medicine, including the regulation of the innate immune system(which includes macrophages, MDSCs, natural killer cells)and adaptive immune system (e.g., CD4+ T cells, CD8+ T cells, regulatory T cells (Treg)), adjusting tumor-associated inflammation. In addition, a combination of active ingredients of herbal medicine and modern nanotechnology restructure tumor immune microenvironment. In recent years, immunological anti-tumor therapy in TCM has been applied on a reasonably large scale both nationally and internationally, and there is potential for further clinical expansion. The investigation of immune modulation mechanisms in Chinese herbal medicine will provide novel perspectives of how herbal medicine controls tumor growth and metastasis, which will contribute to the evolution of tumor research.